2013
DOI: 10.1016/j.jctb.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A problem of Erdős on the minimum number of k -cliques

Abstract: Fifty years ago Erdős asked to determine the minimum number of k-cliques in a graph on n vertices with independence number less than l. He conjectured that this minimum is achieved by the disjoint union of l − 1 complete graphs of size n l−1 . This conjecture was disproved by Nikiforov who showed that the balanced blow-up of a 5-cycle has fewer 4-cliques than the union of 2 complete graphs of size n 2 . In this paper we solve Erdős' problem for (k, l) = (3, 4) and (k, l) = (4, 3). Using stability arguments we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 14 publications
0
44
0
Order By: Relevance
“…Using the flag algebra semidefinite method, we were able to obtain the bound truerightφHom+(scriptA0,R),φ(W4)0.157516,subject to floating point rounding errors. This suggests that the conjecture is true and that there may be a straightforward (but numerically intensive) proof using the semidefinite method and rounding techniques (see for some examples).…”
Section: Concluding Remarks and Open Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the flag algebra semidefinite method, we were able to obtain the bound truerightφHom+(scriptA0,R),φ(W4)0.157516,subject to floating point rounding errors. This suggests that the conjecture is true and that there may be a straightforward (but numerically intensive) proof using the semidefinite method and rounding techniques (see for some examples).…”
Section: Concluding Remarks and Open Problemsmentioning
confidence: 99%
“…Using the flag algebra semidefinite method, we were able to obtain the bound ∀ ∈ Hom + ( 0 , ℝ), ( 4 ) ⩽ 0.157516, subject to floating point rounding errors. This suggests that the conjecture is true and that there may be a straightforward (but numerically intensive) proof using the semidefinite method and rounding techniques (see [1,10,11,14,22] for some examples). The intuition of the recursive construction of , is that at every step we have one part −1 ⧵ that maximizes the density of ⃗ 3 (hence is almost balanced) and another part whose vertices all beat the first part.…”
Section: F I G U R Ementioning
confidence: 99%
“…1 2 ]×[0,1] is a continuous map from a topological 2-disc, mapping its boundary to a path encircling C , 1]. Therefore, as before, the region between these curves is contained in (K 3…”
Section: Distribution Of 3-cliques and 3-anticliquesmentioning
confidence: 88%
“…The case α = 0 of this problem was posed by Erdős more than 50 years ago. Although, recently Das et al [3], and independently Pikhurko [18], solved it for certain values of r and s it is still open in general.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that if the density of independent sets of size r is fixed, the maximum density of s-cliques is achieved when the graph itself is either a clique on a subset of the vertices, or a complement of a clique. On the other hand, the problem of minimizing the clique density seems much harder and has quite different extremal graphs for various values of r and s (at least when α = 0, see [3,13]). Question 7.1.…”
Section: Discussionmentioning
confidence: 99%